Complex band structure and evanescent Bloch wave propagation of periodic nested acoustic black hole phononic structure. (June 2021) - Gao, Nansha; Wang, Baozhu; Lu, Kuan; Hou, Hong
Abstract: In this study, the periodic nested acoustic black hole phononic structure is presented, and different complex band structures and corresponding evanescent Bloch wave propagation are discussed. Vibration transmissions and modes indicated that the corresponding regions of the bandgaps were due to the coupling effect between the Fano-like resonance and Bragg scattering, which also presented the negative mass and stiffness characteristics. Moreover, strain tensors at interface and central sections of the unit cells were used to evaluate the structural instability and failure. Contrast models proved the superiority of the periodic nested acoustic black hole phononic structure for evanescent Bloch wave control and vibration experiments verified its effectiveness. The relevant conclusions can be used in the vibration reduction design of lightweight structure and enrich the relevant research experience on acoustic black hole.